Methods of One-Dimensional Non-Stationary Signal Scanning within Time and Frequency Domain and their Application for Otoacoustic Emission Signal Analysis - Marozas, V. (Elektronika ir Elektrotechnika, 1997)
There were some of the "time- frequency" methods compared in this paper. It is shown that an adaptive optimal Kernel "time- frequency" method is more suitable for the "time- frequency" analysis of evoked otoacoustic emissions than others.